TEACHERS' EFFORTS TO INCREASE ENGLISH LEARNING MOTIVATION THROUGH INTERACTIVE LEARNING - Hafizatun Septi Arizky; Aufa Nabila; Adelia Salsabilla; Muhammad Aripin Ilham; Muhamad Hakim; Abdul Syahid (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Low motivation and passive participation of students in English learning are significant challenges in developing communicative competence at the elementary school level. This study aims to improve student learning motivation through the implementation of interactive learning strategies that include educational games, group discussions, and the use of visual worksheets. Conducted using the Classroom Action Research (CAR) method at Sahabat Alam School, Palangka Raya, this study involved 21 fifth and sixth grade students through two cycles consisting of planning, implementation, observation, and reflection. Data collection was conducted through classroom observations, interviews, and tests to measure changes in learning behavior. The results showed a significant increase in all motivation indicators between Cycle I and Cycle II: student participation increased by 28% (from 58% to 86%), active speaking increased by 29% (from 52% to 81%), group cooperation grew by 28% (from 60% to 88%), and enthusiasm increased by 27% (from 63% to 90%). Qualitatively, students showed increased confidence and courage to interact in English without fear of mistakes. It was concluded that the integration of interactive learning tools effectively changed the classroom dynamics to be more lively and meaningful, so teachers were recommended to maintain this strategy to maintain the consistency of student motivation in the long term. ABSTRAK Rendahnya motivasi dan partisipasi pasif siswa dalam pembelajaran bahasa Inggris menjadi tantangan signifikan dalam pengembangan kompetensi komunikatif di tingkat sekolah dasar. Penelitian ini bertujuan untuk meningkatkan motivasi belajar siswa melalui penerapan strategi pembelajaran interaktif yang meliputi permainan edukatif, diskusi kelompok, dan penggunaan lembar kerja visual. Dilaksanakan dengan metode Penelitian Tindakan Kelas (PTK) di Sekolah Sahabat Alam Palangka Raya, studi ini melibatkan 21 siswa kelas lima dan enam melalui dua siklus yang terdiri dari tahap perencanaan, pelaksanaan, pengamatan, dan refleksi. Pengumpulan data dilakukan melalui observasi kelas, wawancara, dan tes untuk mengukur perubahan perilaku belajar. Hasil penelitian menunjukkan peningkatan signifikan pada seluruh indikator motivasi antara Siklus I dan Siklus II: partisipasi siswa meningkat sebesar 28% (dari 58% menjadi 86%), keaktifan berbicara naik 29% (dari 52% menjadi 81%), kerja sama kelompok bertumbuh 28% (dari 60% menjadi 88%), dan antusiasme meningkat 27% (dari 63% menjadi 90%). Secara kualitatif, siswa menunjukkan peningkatan kepercayaan diri dan keberanian untuk berinteraksi dalam bahasa Inggris tanpa rasa takut salah. Disimpulkan bahwa integrasi alat pembelajaran interaktif efektif mengubah dinamika kelas menjadi lebih hidup dan bermakna, sehingga guru direkomendasikan untuk mempertahankan strategi ini guna menjaga konsistensi motivasi siswa dalam jangka panjang.